A green and general strategy for the synthesis of hollow Ag/CdS nanocomposites for superior SERS performance. Issue 24 (3rd June 2019) - Li, Shanshan; Wang, Qi; Song, Xinyu; Bu, Yuxiang
Abstract : In this study, we developed a convenient, environmentally friendly approach for the fabrication of hollow Ag/CdS composites, which presented superior SERS performance. Abstract : Semiconductor-based materials as SERS-active substrates have gained significant attention because of their superior properties. However, to date, only few studies have been reported on the SERS performance of substrates fabricated using CdS-based composites. In this study, hollow sphere-like Ag/CdS nanocomposites (NCs) with multi-hot spots were successfully synthesized via a room-temperature solution route without the addition of surfactant. Especially, note that in our strategy, the cadmium ions in an aqueous solution originating from the self-template core dissolved with acid were retrieved and recycled via a simple approach, avoiding the wastage of resources and environmental problems. Moreover, a strong electromagnetic enhancement between two neighboring Ag nanoparticles (NPs) on the CdS sphere-like surface could be achieved by conveniently adjusting the amount of the AgNO3 reagent. Note that the as-prepared substrate with low loading of Ag presented superior SERS performance with the ultralow limit of detection of 10 −12 mol L −1 for R6G and CV, much higher than that of many recently reported composite substrates. These significantly enhanced SERS effects are attributed to the combination of several contributions, including plasmonic coupling between Ag NPs, synergistic charge-transfer resonances in the Ag/CdS/dye molecule system, and cadmium defect-induced electrostatic forces. As a consequence, the present study not only develops a convenient, environmentally friendly approach for the fabrication of noble/CdS composites but also indicates the promising potential application of these composites as ideal SERS substrates in the detection of organic pollutants.